Packaging materials and containers
The packaging material with a urethane adhesive layer and ion capture agents addresses corrosion issues in aluminum vapor deposition layers by capturing ionic surfactants, maintaining the metallic luster and appearance.
Patent Information
- Application Number
- JP2020191218
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-25
- Filing Date
- 2020-11-17
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2040-11-17
Smart Images

Figure 0007622404000001 
Figure 0007622404000002 
Figure 0007622404000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a packaging material and a packaging container suitable for refill pouches for shampoo, fabric softener, and the like. [Background technology]
[0002] Multi-layer laminates of various plastic films are widely used as packaging materials for food, clothing, cosmetics, miscellaneous goods, etc. The adhesives used for lamination are mainly reactive adhesives that use a polyol component as the base agent and a polyisocyanate component as the curing agent, and form a urethane adhesive layer. In recent years, from the viewpoints of content protection and design, packaging materials using aluminum vapor-deposited films have been increasing, but when packaging contents that contain ionic surfactant components such as dialkylammonium salts, such as shampoos and fabric softeners, there is a problem that the aluminum vapor-deposited layer deteriorates and loses its metallic luster while on display at the store. At home, too, if packaging materials are stored with the above-mentioned ionic surfactant components attached to the outside, there is a similar problem of the aluminum vapor-deposited layer deteriorating.
[0003] In response to the above-mentioned problems, for example, Patent Document 1 describes a polyol / polyisocyanate-based adhesive containing a carboxyl group-containing compound having a specific SP value in a predetermined amount range, and a laminate film having an adhesive layer formed from the adhesive, which exhibits excellent laminate appearance and aluminum vapor deposition layer disappearance properties. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2017 / 221661 Summary of the Invention [Problem to be solved by the invention]
[0005] However, the adhesive described in Patent Document 1 has a problem that the viscosity is likely to increase, particularly when the solid content concentration of the adhesive is increased or when it is made a solventless adhesive, and deterioration of the laminate appearance due to poor coating is unavoidable. Therefore, an object of the present invention is to provide a packaging material and a packaging container that are excellent in laminate appearance and that suppress deterioration of the aluminum vapor deposition layer even after long-term storage when contents containing an ionic surfactant component are packaged or when the above component adheres to the outside of the packaging material. [Means for solving the problem]
[0006] As a result of intensive research aimed at solving the above problems, the present inventors have found that the above problems can be solved by the embodiments described below, and have thus completed the present invention.
[0007] An embodiment of the present invention relates to a packaging material having at least a configuration in which a first substrate, a urethane adhesive layer, and a second substrate are laminated in this order from the outside, wherein at least one of the first substrate and the second substrate is a substrate having an aluminum vapor-deposited layer, the urethane adhesive layer contains an ion scavenger (X), and the urethane adhesive layer is provided in contact with the aluminum vapor-deposited layer.
[0008] Another embodiment of the present invention relates to the above packaging material, wherein the urethane adhesive layer is a cured product of an adhesive composition containing a polyol component (A) and a polyisocyanate component (B).
[0009] Another embodiment of the present invention relates to the above packaging material, wherein the polyol component (A) includes at least one selected from the group consisting of polyester polyols and polyether polyols.
[0010] Another embodiment of the present invention relates to the above packaging material, wherein the ion scavenger (X) is an inorganic compound.
[0011] Another embodiment of the present invention relates to the above packaging material, wherein the average particle size of the ion scavenger (X) is 0.1 to 1.0 μm.
[0012] Another embodiment of the present invention relates to the above packaging material, wherein the content of the ion scavenger (X) is 0.2 to 10% by mass relative to the mass of the urethane adhesive layer.
[0013] Another embodiment of the present invention relates to the above packaging material, wherein the ion scavenger (X) is hydrotalcite.
[0014] Another embodiment of the present invention relates to the above packaging material, wherein the first substrate and the second substrate have a polyolefin resin layer.
[0015] Another embodiment of the present invention relates to a packaging container formed at least in part from the packaging material described above. Effect of the Invention
[0016] According to the present invention, when contents containing an ionic surfactant component are packaged or when the above-mentioned component adheres to the outside of the packaging material, even after long-term storage, deterioration of the aluminum vapor deposition layer is suppressed, and it is possible to provide a packaging material and a packaging container that have excellent laminate appearance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] <Packaging materials> The packaging material of the present invention is characterized in that it has at least a configuration in which a first substrate, a urethane adhesive layer, and a second substrate are laminated in this order from the outside, at least one of the first substrate and the second substrate is a substrate having an aluminum vapor-deposited layer, the urethane adhesive layer contains an ion trapping agent (X), and the urethane adhesive layer is provided in contact with the aluminum vapor-deposited layer. By having the urethane adhesive layer containing the ion trapping agent (X) in contact with the aluminum vapor-deposited layer, it is possible to efficiently trap ionic surfactant components that penetrate into the vicinity of the vapor-deposited layer, and to suppress deterioration of the vapor-deposited layer. The present invention will be described in detail below.
[0018] <Urethane adhesive layer> The urethane adhesive layer in the present invention contains an ion scavenger (X). [Ion trap (X)] The ion scavenger (X) means an organic or inorganic compound having the function of adsorbing, capturing, or exchanging ions, and may be a natural or artificial product. The ion scavenger (X) may be an anion scavenger, a cation scavenger, or a cation-scavenger. A cation-scavenger can capture both anions and cations.
[0019] Examples of the inorganic compound ion trapping agent include zirconium-based compounds, antimony-based compounds, titanium-based compounds, tin-based compounds, bismuth-based compounds, aluminum-based compounds, magnesium-based compounds, rare earth-based compounds, and hydrotalcite-based compounds. Examples of organic compound ion scavengers include nitrogen-containing heterocyclic compounds such as imidazole compounds, triazole compounds, tetrazole compounds, bipyridyl compounds, and quinol compounds; phenolic compounds such as hydroxyanthraquinone compounds and polyphenol compounds; carboxyl group-containing aliphatic compounds such as citric acid; and epoxy compounds such as epoxidized soybean oil and epoxidized linseed oil. The ion scavengers may be used alone or in combination of two or more kinds.
[0020] Among these, from the viewpoint of retaining ionic compounds, the ion trapping agent (X) is preferably an inorganic compound, more preferably a composite inorganic compound, and even more preferably a hydrotalcite-based compound. Hydrotalcite-based compounds are particularly preferred in terms of excellent ion trapping ability and suppressing corrosion of the aluminum vapor deposition layer. The hydrotalcite-based compound is not particularly limited, and conventionally known compounds can be used. Examples of the ion trapping agent of the hydrotalcite-based compound include DHT-4A, DHT-4A-2, and DHT-4C manufactured by Kyowa Chemical Industry Co., Ltd., and IXE-500, IXE-700F, and IXEPLAS-B1 manufactured by Toagosei Co., Ltd.
[0021] From the viewpoint of ion trapping ability and transparency of the adhesive layer, the ion trapping agent (X) is preferably particles having an average particle size of 10 μm or less. When the ion trapping agent (X) is particles having an average particle size of 10 μm or less, it has little effect on the coatability of the adhesive, and the resulting packaging material has excellent appearance after lamination and excellent corrosion inhibition ability of the aluminum vapor deposition layer. The average particle size of the ion scavenger (X) is preferably 0.01 to 5.0 μm, more preferably 0.05 to 3.0 μm, and even more preferably 0.1 to 1.0 μm. The average particle size of the ion scavenger can be measured by dispersing the particles in a solvent (water, organic solvent, etc.) using a NICOMP 380ZLS (manufactured by PARTICLE SIZING SYSTEMS).
[0022] The content of the ion trapping agent (X) is not particularly limited, but from the viewpoints of corrosion inhibition of the aluminum vapor deposition layer, properties and coatability as an adhesive, and appearance after lamination, it is preferably 0.1 to 20 mass% relative to the mass of the urethane adhesive layer, more preferably 0.2 to 10 mass%. If it is 0.1 mass% or more, corrosion of the aluminum vapor deposition layer is further inhibited, and if it is 20 mass% or less, the effect on properties and coatability as an adhesive is small and the appearance after lamination is excellent, so it is preferable.
[0023] [Adhesive composition] The urethane adhesive layer in the present invention is preferably a cured product of an adhesive composition containing a polyol component (A) and a polyisocyanate component (B).
[0024] (Polyol component (A)) The polyol component (A) used in the present invention is not particularly limited, and examples thereof include polyester polyols, polyether polyols, polyurethane polyols, polyesteramide polyols, acrylic polyols, polycarbonate polyols, polycaprolactone polyols, polyvalerolactone polyols, polyolefin polyols, polyhydroxyalkanes, castor oil, and mixtures thereof, as well as ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 3-methyl-5-pentanediol, and 1,6-hexanediol. Glycols such as neopentyl glycol, methylpentane glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, bishydroxyethoxybenzene, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, and triethylene glycol; polyalkylene glycols having a number average molecular weight of 200 to 3,000; trifunctional or tetrafunctional aliphatic alcohols such as glycerin, trimethylolpropane, and pentaerythritol; and polyols obtained by adding the above-mentioned glycols or polyols to the above-mentioned trifunctional or tetrafunctional aliphatic alcohols. These may be used alone or in combination of two or more kinds.
[0025] The polyol component preferably contains a polyester polyol or a polyether polyol. The polyester polyol may be a dibasic acid such as terephthalic acid, isophthalic acid, naphthalenedicarboxylic acid, phthalic anhydride, adipic acid, azelaic acid, sebacic acid, succinic acid, glutaric acid, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, maleic anhydride, or itaconic anhydride, or a dialkyl ester thereof, or a mixture thereof (hereinafter also referred to as a carboxyl group component); diols such as ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, triethylene glycol, butylene glycol, neopentyl glycol, dineopentyl glycol, trimethylolpropane, glycerin, 1,6-hexanediol, 1,4-butanediol, 1,4-cyclohexanedimethanol, 3-methyl-1,5-pentanediol, 3,3'-dimethylolheptane, 1,9-nonanediol, polyoxyethylene glycol, polyoxypropylene glycol, polytetramethylene ether glycol, polyether polyol, polycarbonate polyol, polyolefin polyol, acrylic polyol, polyurethane polyol, or mixtures thereof (hereinafter also referred to as hydroxyl group components); or polyester polyols obtained by ring-opening polymerization of lactones such as polycaprolactone, polyvalerolactone, and poly(β-methyl-γ-valerolactone). The above carboxyl group components and hydroxyl group components may be used in combination of two or more kinds.
[0026] Examples of polyether polyols include polyether diols and polyether triols. Examples of such polyether polyols include polyether diols obtained by polymerizing an oxirane compound such as ethylene oxide, propylene oxide, butylene oxide, or tetrahydrofuran with a bifunctional low molecular weight polyol such as water, ethylene glycol, or propylene glycol as an initiator; and polyether triols obtained by polymerizing an oxirane compound such as ethylene oxide, propylene oxide, butylene oxide, or tetrahydrofuran with a low molecular weight triol such as trimethylolpropane or glycerin as an initiator.
[0027] The polyester polyol or polyether polyol may be a polyester urethane polyol or a polyether urethane polyol which has been further reacted with a diisocyanate, or may be a polyether urethane polyol which has been further reacted with an acid anhydride. Examples of the diisocyanate include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, 1,5-naphthalene diisocyanate, hexamethylene diisocyanate, and hydrogenated diphenylmethane diisocyanate. Examples of the acid anhydride include pyromellitic anhydride, mellitic anhydride, trimellitic anhydride, and trimellitic ester anhydride. Examples of the trimellitic ester anhydride include ethylene glycol bisanhydrotrimellitate and propylene glycol bisanhydrotrimellitate.
[0028] The number average molecular weight of the polyol component (A) is preferably 500 to 100,000, more preferably 600 to 50,000, and further preferably 700 to 30,000. The acid value of the polyol component (A) is not particularly limited, but is preferably 0 to 50 mgKOH / g, and more preferably 0 to 40 mgKOH / g. The hydroxyl value of the polyol component (A) is not particularly limited, but is preferably 1 to 200 mgKOH / g, and more preferably 3 to 150 mgKOH / g.
[0029] (Polyisocyanate component (B)) The polyisocyanate component (B) is not particularly limited, and examples thereof include aliphatic diisocyanates such as trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, 1,2-propylene diisocyanate, 1,2-butylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, 2,4,4- or 2,2,4-trimethylhexamethylene diisocyanate, and 2,6-diisocyanate methyl caproate; 1,4-cyclohexane Diisocyanates, alicyclic diisocyanates such as 1,3-cyclohexane diisocyanate, 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), methyl 2,4-cyclohexane diisocyanate, methyl 2,6-cyclohexane diisocyanate, 1,4-bis(isocyanatomethyl)cyclohexane, 1,3-bis(isocyanatomethyl)cyclohexane; m-phenylene diisocyanate, p Aromatic diisocyanates such as 1,3- or 1,4-xylylene diisocyanate or mixtures thereof, ω,ω'-diisocyanate-1,3-diisocyanate, ω,ω'-diisocyanate-1,4-diphenyl diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4- or 2,6-tolylene diisocyanate or mixtures thereof, 4,4'-toluidine diisocyanate, dianisidine diisocyanate, 4,4'-diphenyl ether diisocyanate, etc. arylaliphatic diisocyanates such as 1,3- or 1,4-bis(1-isocyanato-1-methylethyl)benzene or mixtures thereof; organic triisocyanates such as triphenylmethane-4,4',4"-triisocyanate, 1,3,5-triisocyanatobenzene, 2,4,6-triisocyanatotoluene, and organic tetraisocyanates such as 4,4'-diphenyldimethylmethane-2,2'-5,5'-tetraisocyanate;Examples of the polyisocyanate include dimers, trimers, biurets, and allophanates derived from the above polyisocyanate monomers, and polyisocyanates having a 2,4,6-oxadiazinetrione ring obtained from carbon dioxide gas and the above polyisocyanate monomers. The polyisocyanate component (B) may be used alone or in combination of two or more kinds.
[0030] The polyisocyanate component may be an adduct of the above-mentioned polyisocyanate with a glycol. Examples of the glycol include low molecular weight polyols having a molecular weight of less than 200, such as ethylene glycol, propylene glycol, butylene glycol, hexylene glycol, neopentyl glycol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 3,3'-dimethylolpropane, cyclohexanedimethanol, diethylene glycol, triethylene glycol, dipropylene glycol, glycerol, trimethylolpropane, pentaerythritol, and sorbitol; and polypropylene glycol, polyester polyols, polyether ester polyols, polyester amide polyols, polycaprolactone polyols, polyvalerolactone polyols, acrylic polyols, polycarbonate polyols, polyhydroxy alkanes, castor oil, and polyurethane polyols.
[0031] When an adduct of a glycol to a polyisocyanate is used, it is preferably a reaction product of a polyisocyanate and a polypropylene glycol, more preferably a reaction product of an aromatic polyisocyanate and a polypropylene glycol. When the polyisocyanate component contains an aromatic skeleton, heat resistance is improved, and lifting due to folding of the heat-sealed portion can be suppressed. The number average molecular weight of the polypropylene glycol is preferably 200 to 3,000.
[0032] The adhesive composition may further contain known adhesive components in the base agent or curing agent. (Reaction accelerator) The adhesive composition may contain, for example, a reaction accelerator. Examples of reaction accelerators include metal catalysts such as dibutyltin diacetate, dibutyltin dilaurate, dioctyltin dilaurate, and dibutyltin dimaleate; tertiary amines such as 1,8-diaza-bicyclo(5,4,0)undecene-7, 1,5-diazabicyclo(4,3,0)nonene-5, and 6-dibutylamino-1,8-diazabicyclo(5,4,0)undecene-7; and reactive tertiary amines such as triethanolamine. These may be used alone or in any combination of two or more.
[0033] (Silane coupling agent) The adhesive composition may contain a silane coupling agent from the viewpoint of improving the adhesive strength to metal-based materials such as metal foil. Examples of the silane coupling agent include trialkoxysilanes having a vinyl group, such as vinyltriethoxysilane and vinyltriethoxysilane; trialkoxysilanes having an amino group, such as 3-aminopropyltriethoxysilane and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane; trialkoxysilanes having a glycidyl group, such as 3-glycidoxypropyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)-ethyltrimethoxysilane and 3-glycidoxypropyltriethoxysilane. These may be used alone or in any combination of two or more. The content of the silane coupling agent is preferably 0.1 to 5 mass %, more preferably 0.2 to 3 mass %, based on the total polyol component. By setting the content within the above range, the adhesive strength to the metal foil can be improved.
[0034] (Phosphoric acid or phosphoric acid derivatives) The adhesive composition may contain phosphoric acid or a phosphoric acid derivative from the viewpoint of improving the adhesive strength to metal-based materials such as metal foil. The phosphoric acid may be any one having at least one free oxygen acid, and examples thereof include phosphoric acids such as hypophosphorous acid, phosphorous acid, orthophosphoric acid, and hypophosphoric acid; and condensed phosphoric acids such as metaphosphoric acid, pyrophosphoric acid, tripolyphosphoric acid, polyphosphoric acid, and ultraphosphoric acid. Examples of phosphoric acid derivatives include those obtained by partially esterifying the above-mentioned phosphoric acid with alcohols while leaving at least one free oxygen acid. Examples of the alcohols include aliphatic alcohols such as methanol, ethanol, ethylene glycol, and glycerin; and aromatic alcohols such as phenol, xylenol, hydroquinone, catechol, and phloroglucinol. These may be used alone or in any combination of two or more. The content of phosphoric acid or a derivative thereof is preferably 0.01 to 10 mass %, more preferably 0.05 to 5 mass %, and even more preferably 0.05 to 1 mass %, based on the solid content of the adhesive composition.
[0035] (Leveling agent, defoamer) The adhesive composition may contain a known leveling agent or defoaming agent for the purpose of improving the appearance of the laminate. Examples of the leveling agent include polyether-modified polydimethylsiloxane, polyester-modified polydimethylsiloxane, aralkyl-modified polymethylalkylsiloxane, polyester-modified hydroxyl-containing polydimethylsiloxane, polyetherester-modified hydroxyl-containing polydimethylsiloxane, acrylic copolymer, methacrylic copolymer, polyether-modified polymethylalkylsiloxane, acrylic acid alkyl ester copolymer, methacrylic acid alkyl ester copolymer, and lecithin. Examples of the defoaming agent include silicone resins, silicone solutions, and copolymers of alkyl vinyl ethers, alkyl acrylates, and alkyl methacrylates. These can be used alone or in any combination of two or more. The content of the leveling agent and the antifoaming agent is preferably 0.001 to 1 mass %, and more preferably 0.005 to 0.5 mass %, based on the solid content of the adhesive composition.
[0036] (Other additives) The adhesive composition may contain various additives within the range that does not impair the effects of the present invention. Examples of additives include inorganic fillers such as silica, alumina, mica, talc, aluminum flakes, and glass flakes, layered inorganic compounds, stabilizers (antioxidants, heat stabilizers, ultraviolet absorbers, hydrolysis inhibitors, etc.), rust inhibitors, thickeners, plasticizers, antistatic agents, lubricants, antiblocking agents, colorants, fillers, crystal nucleating agents, and catalysts for adjusting the curing reaction.
[0037] The adhesive composition may be diluted with an organic solvent to adjust the viscosity to an appropriate level. As the organic solvent, those inactive to the polyisocyanate component, such as esters such as ethyl acetate, ketones such as methyl ethyl ketone, and aromatic hydrocarbons such as toluene and xylene, are preferably used, and can be appropriately selected and used.
[0038] <First substrate and second substrate> At least one of the first substrate and the second substrate used in the present invention has an aluminum vapor-deposited layer. Since the vapor-deposited layer is in contact with the above-mentioned urethane adhesive layer, ionic surfactant components that have permeated from the contents are efficiently captured by the ion scavenger in the adhesive layer, and deterioration of the aluminum vapor-deposited layer is suppressed.
[0039] [First substrate] The first substrate may be a film- or sheet-like plastic substrate generally used for packaging materials, or may be a laminate of these. When the first substrate has an aluminum vapor deposition layer, the vapor deposition layer is provided on the surface of the first substrate, and is disposed on the surface facing the urethane adhesive layer when the first substrate is laminated with a second substrate described later via the urethane adhesive layer. Examples of the plastic substrate include films of thermoplastic resins and thermosetting resins, and preferably films of thermoplastic resins. Examples of the thermoplastic resin include polyolefin resins, polyester resins, polyamide resins, polystyrene resins, vinyl chloride resins, vinyl acetate resins, AS resins, ABS resins, acrylic resins, acetal resins, polycarbonate resins, cellulose resins, and cellulose-based plastics.
[0040] More specifically, polyolefin resin films such as polyethylene (PE) and biaxially oriented polypropylene (OPP), polyester resin films such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), and polylactic acid (PLA), polystyrene resin films, polyamide resin films such as nylon 6 and poly-p-xylylene adipamide (MXD6 nylon), polycarbonate resin films, polyacrylonitrile resin films, polyimide resin films, cellophane films, laminates thereof (for example, nylon 6 / MXD6 / nylon 6, nylon 6 / ethylene-vinyl alcohol copolymer / nylon 6) and mixtures thereof, etc. are used. Among them, those having mechanical strength and dimensional stability are preferable. The thickness of the plastic film is preferably 5 μm or more and 200 μm or less, more preferably 10 μm or more and 100 μm or less, and further preferably 10 μm or more and 50 μm or less.
[0041] When the first substrate is a laminate, it is preferable that the first substrate is laminated via an adhesive layer. The method for forming the adhesive layer is not limited, and the adhesive layer can be formed by a known method using a known adhesive. The first substrate may contain additives such as antistatic agents and ultraviolet protection agents as necessary, and the substrate surface may be subjected to a corona treatment or low-temperature plasma treatment.
[0042] [Second substrate] The second substrate may be, for example, a substrate such as the substrates listed as the first substrate above, or a sealant substrate, and may be a laminate of these. When the second substrate has an aluminum deposition layer, the deposition layer is provided on the surface of the second substrate, and is disposed on the surface facing the urethane adhesive layer when the second substrate is laminated to the first substrate via the urethane adhesive layer. Examples of sealant base materials include polyethylenes such as low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), and high-density polyethylene (HDPE), acid-modified polyethylene, solid polypropylene (CPP), acid-modified polypropylene, copolymerized polypropylene, ethylene-vinyl acetate copolymer, ethylene-(meth)acrylic acid ester copolymer, ethylene-(meth)acrylic acid copolymer, and ionomer. The second substrate is preferably a sealant substrate, which comprises a polyolefin.
[0043] The thickness of the second substrate is not particularly limited, and is preferably 10 μm to 150 μm, more preferably 20 μm to 70 μm, in consideration of processability into packaging containers, heat sealability, etc. By providing the second substrate with irregularities having height differences of about several μm, slipperiness and tearability of the packaging material can be imparted.
[0044] The second substrate may contain additives such as antistatic agents and ultraviolet protection agents as necessary, and the substrate surface may be corona-treated or low-temperature plasma-treated. In addition, a sealant layer may be provided on the outermost layer of the second substrate and the outermost layer of the packaging material, and may be either a heat sealant layer or a cold sealant layer.
[0045] [Print layer] The packaging material of the present invention may further have a printed layer. The printed layer is a layer that forms any printed pattern for the purpose of decoration, imparting aesthetics, displaying the contents, expiration date, manufacturer or seller, etc., and includes a solid printed layer. The printed layer can be provided, for example, between the substrate and the adhesive layer, and may be provided on the entire surface or part of the substrate. The printing layer can be formed using a conventionally known pigment or dye, or may be formed using a printing ink containing a pigment or dye, and the method of formation is not particularly limited. The printing layer may be formed of a single layer or multiple layers. The thickness of the printed layer is preferably 0.1 μm or more and 100 μm or less, more preferably 0.1 μm or more and 10 μm or less, and even more preferably 1 μm or more and 5 μm or less.
[0046] <Manufacturing of packaging materials> The method for producing the packaging material of the present invention is not particularly limited, and for example, a method of bonding a first substrate and a second substrate with an adhesive composition may be mentioned. The adhesive composition may be applied to at least one of the first substrate and the second substrate. Examples of devices for applying the adhesive composition include a comma coater, a dry laminator, a roll knife coater, a die coater, a roll coater, a bar coater, a gravure roll coater, a reverse roll coater, a blade coater, a gravure coater, and a microgravure coater. The amount of solids of the adhesive composition to be applied is not particularly limited and can be appropriately selected depending on the application. It is usually 0.5 to 6 g / m 2 In the case where the adhesive composition is a solventless type, the adhesive composition is in the range of 1 to 3 g / m 2 , 1 to 5 g / m for solvent-based 2 The range is preferably used.
[0047] From the viewpoint of recyclability, the first and second substrates are preferably substrates of the same resin system, and are preferably both polyolefin resins. Examples of packaging materials with such a combination include, but are not limited to, the following configurations. PET / urethane adhesive layer / aluminum vapor deposition layer / PE OPP / urethane adhesive layer / aluminum vapor deposition layer / OPP HDPE / urethane adhesive layer / aluminum vapor deposition layer / PE Nylon (NY) / Urethane adhesive layer / PET / Aluminum vapor deposition layer / Urethane adhesive layer / PE ·PET / urethane adhesive layer / aluminum vapor deposition layer / PET / urethane adhesive layer / PE
[0048] <Packaging container> The packaging container of the present invention is not limited in shape as long as at least a part of it is made of the above-mentioned packaging material. For example, the packaging container may be a pouch formed by heat-sealing two sheets of packaging material with the second substrates facing each other. The packaging container of the present invention is excellent in inhibiting corrosion of the aluminum vapor deposition layer when the content contains an ionic surfactant component, and therefore can be suitably used as a refill pouch for shampoo or fabric softener. EXAMPLES
[0049] The present invention will be specifically described below with reference to examples and comparative examples. In the examples and comparative examples, "parts" and "%" mean "parts by mass" and "% by mass" unless otherwise specified.
[0050] <Acid value (AV) measurement> Approximately 1 g of sample (polyester polyol solution) was precisely weighed and placed in a stoppered Erlenmeyer flask, and 100 ml of a toluene / ethanol (volume ratio: toluene / ethanol = 2 / 1) mixture was added to dissolve it. Phenolphthalein test solution was added as an indicator and the solution was held for 30 seconds. After that, the solution was titrated with 0.1N alcoholic potassium hydroxide solution until it turned a light pink color, and the acid value (mgKOH / g) was calculated using the following formula. Acid value (mgKOH / g)=(5.611×a×F) / S Where S is the amount of sample taken (g) a: Amount of 0.1N alcoholic potassium hydroxide solution consumed (ml) F: Potency of 0.1N alcoholic potassium hydroxide solution
[0051] <Measurement of hydroxyl value (OHV)> Approximately 1 g of sample (polyester polyol, hydroxyl-containing urethane resin, etc.) was precisely weighed and placed in a stoppered Erlenmeyer flask, and 100 ml of a toluene / ethanol (volume ratio: toluene / ethanol = 2 / 1) mixture was added and dissolved. Exactly 5 ml of an acetylating agent (a solution of 25 g of acetic anhydride dissolved in pyridine to a volume of 100 ml) was then added and stirred for approximately 1 hour. Phenolphthalein test solution was added as an indicator and allowed to stand for 30 seconds. After that, the solution was titrated with 0.1 N alcoholic potassium hydroxide solution until it turned a light pink color, and the hydroxyl value (mgKOH / g) was calculated using the following formula. Hydroxyl value (mgKOH / g) = [{(ba) × F × 28.05} / S] + D Where S is the amount of sample taken (g) a: Amount of 0.1N alcoholic potassium hydroxide solution consumed (ml) b: Amount of 0.1N alcoholic potassium hydroxide solution consumed in the blank experiment (ml) F: Potency of 0.1N alcoholic potassium hydroxide solution D: Acid value (mgKOH / g)
[0052] <Measurement of number average molecular weight (Mn)> The number average molecular weight (Mn) was measured using a GPC (gel permeation chromatography) "Shodex GPC System-21" manufactured by Showa Denko Co., Ltd. GPC is a liquid chromatography that separates and quantifies substances dissolved in a solvent based on the difference in their molecular size. Tetrahydrofuran was used as the solvent, and the molecular weight was determined in terms of polystyrene.
[0053] <Synthesis of polyol component> (Synthesis of Polyol A-1) 425.6 parts of isophthalic acid, 160.4 parts of adipic acid, 81.8 parts of ethylene glycol, 228.5 parts of neopentyl glycol, and 103.7 parts of 1,6-hexanediol were charged into a reaction vessel and subjected to an esterification reaction at 200 to 230°C for 6 hours. After a predetermined amount of water was distilled off, 0.01 parts of tetraisobutyl titanate was added and the pressure was gradually reduced. The mixture was heated at 5 hPa and 230 to 250°C for 6 hours to distill off a portion of the glycol component and perform an ester exchange reaction to obtain a polyester polyol intermediate. The molar ratio of the dicarboxylic acid component and the diol component used in the reaction (moles of isophthalic acid / moles of adipic acid / moles of ethylene glycol / moles of neopentyl glycol / moles of 1,6-hexanediol) was 2.6 mol / 1.1 mol / 1.3 mol / 2.2 mol / 0.88 mol. Next, 4.5 parts of trimellitic anhydride was added to 300 parts of the obtained polyester polyol intermediate, and the mixture was kept at 160° C. for 2 hours to obtain a polyester polyol (polyol A-1) having a number average molecular weight of 10,000 and an acid value of 8.1 mgKOH / g. The obtained polyester polyol was adjusted to a solid content concentration of 50% with ethyl acetate to obtain a solution of polyol A-1.
[0054] (Synthesis of Polyol A-2) 115 parts of isophthalic acid, 304 parts of adipic acid, 305 parts of diethylene glycol, and 75 parts of neopentyl glycol were charged into a reaction vessel, and the mixture was heated to 150 to 240°C to carry out an esterification reaction. After a certain amount of water was distilled off, the pressure was gradually reduced, and the mixture was heated at 20 hPa and 200°C for 30 minutes to obtain a polyester polyol (polyol A-2) having a number average molecular weight of 800 and an acid value of 0.4 mgKOH / g.
[0055] (Synthesis of Polyol A-3) 12 parts of bifunctional polypropylene glycol with a number average molecular weight of about 2,000, 38 parts of bifunctional polypropylene glycol with a number average molecular weight of about 400, 3 parts of dipropylene glycol, and 18 parts of tolylene diisocyanate were charged into a reaction vessel, and the mixture was heated at 80 to 90°C for 3 to 5 hours while stirring under a nitrogen gas flow to carry out a urethane reaction. During the urethane reaction, 0.1% of dibutyltin dilaurate (DBTDL) was added as a reaction catalyst to promote the reaction, and polyether urethane polyol (polyol A-3) was obtained. The obtained polyether urethane polyol was adjusted to a solid content concentration of 75% with ethyl acetate to obtain a solution of polyol A-3.
[0056] <Synthesis of polyisocyanate component> (Synthesis of Polyisocyanate B-1) A reaction vessel was charged with 300 parts of polypropylene glycol having a number average molecular weight of about 400, 400 parts of polypropylene glycol having a number average molecular weight of about 2,000, 200 parts of a triol having a number average molecular weight of about 400 obtained by adding polypropylene glycol to glycerin, 500 parts of 4,4'-diphenylmethane diisocyanate, and 500 parts of 2,4-diphenylmethane diisocyanate. The mixture was heated at 70-80°C for 3 hours while stirring under a nitrogen gas flow to carry out a urethane reaction, and a polyisocyanate having a number average molecular weight of about 600 (Polyisocyanate B-1) was obtained.
[0057] (Synthesis of Polyisocyanate B-2) 23 parts of bifunctional polypropylene glycol having a number average molecular weight of about 2,000, 18 parts of bifunctional polypropylene glycol having a number average molecular weight of about 400, 2 parts of trifunctional polypropylene glycol having a number average molecular weight of about 400, and 30 parts of 4,4'-diphenylmethane diisocyanate were charged into a reaction vessel, and the mixture was heated at 70 to 80°C for 4 to 7 hours while stirring under a nitrogen gas flow to carry out a urethane reaction. After the reaction was completed, 7 parts of a trimethylolpropane adduct of tolylene diisocyanate was mixed in. The mixture was diluted with ethyl acetate to a solid concentration of 75%, to obtain a solution of polyisocyanate B-2 containing polyether urethane polyisocyanate.
[0058] <Production of Adhesive Composition> (Formulation Example 1) Adhesive Composition 1 100 parts of Polyol A-1 solution, 10 parts of Desmodur L75 (manufactured by Sumika Covestro Urethane Co., Ltd., trimethylolpropane adduct of toluene diisocyanate, NCO group content 13%, solids concentration 75%), 5 parts of DHT-4A (manufactured by Kyowa Chemical Industry Co., Ltd., hydrotalcite-based ion scavenger, average particle size 0.45 μm), 0.1 parts of γ-glycidoxypropyltriethoxysilane, and 94 parts of ethyl acetate were mixed to obtain adhesive composition 1 with a solids concentration of 30%.
[0059] (Formulation Examples 2 to 11) Adhesive Compositions 2 to 11 Adhesive compositions 2 to 11 were obtained in the same manner as adhesive composition 1, except that the ingredients and amounts were changed as shown in Table 1. Adhesive compositions 4 and 6 are solventless.
[0060] [Table 1]
[0061] The abbreviations in Table 1 are as follows: Desmodur L75: Sumika Covestro Urethane Co., Ltd., toluene diisocyanate trimethylolpropane adduct, NCO group content 13%, solids concentration 75% DHT-4A: Kyowa Chemical Industry Co., Ltd., hydrotalcite-based ion scavenger, average particle size 0.45 μm IXE-550: Toagosei Co., Ltd., hydrotalcite-based ion scavenger, average particle size 1.5 μm IXE-700D: Toagosei Co., Ltd., hydrotalcite-based ion scavenger, average particle size 6μm IXEPLAS-A2: Toagosei Co., Ltd., hydrotalcite-based ion scavenger, average particle size 0.2 μm KL-110: Kao, 1-methylimidazole O-130P: ADEKA, epoxidized soybean oil SMA1000: Cray Valley, styrene / maleic anhydride = 1 / 1 copolymer
[0062] <Production of packaging material (three-layer structure A)> [Example 1] Packaging material 1 Adhesive composition 1 was applied to a nylon film (ONBC, 15 μm thick, manufactured by Unitika Ltd.) at room temperature using a gravure coater, and the solvent was evaporated to form an adhesive layer. The adhesive layer was then bonded to the vapor-deposited surface of an aluminum-deposited polyester film (VM-PET1510, 12 μm thick, manufactured by Toray Advanced Film Co., Ltd.) to obtain an intermediate laminate. The solid content of adhesive composition 1 was 3.5 g / m 2 Next, the adhesive composition 1 was applied to the polyester surface of the intermediate laminate in the same manner as above, and after the solvent was evaporated, the applied surface was bonded to an unstretched polyethylene film (TUX-FCD, manufactured by Mitsui Chemicals Tocello, Inc., thickness 50 μm) to obtain a laminate. The obtained laminate was kept at 40° C. for 4 days to harden the adhesive layer, and a packaging material 1 having a structure of nylon (hereinafter, NY) film / urethane adhesive layer (containing ion scavenger) / aluminum vapor deposition layer / polyester (hereinafter, PET) film / urethane adhesive layer (containing ion scavenger) / unstretched polyethylene (hereinafter, PE) film was obtained. The nylon film is the first substrate, and the aluminum vapor deposition layer / polyester film / urethane adhesive layer (containing an ion scavenger) / unstretched polyethylene film corresponds to the second substrate having an aluminum vapor deposition layer.
[0063] [Examples 2, 3, and 9-13, Comparative Example 1] Packaging materials 2, 3, 5, and 7-11 Packaging materials 2, 3, 5 and 7 to 11 were obtained in the same manner as packaging material 1, except that adhesive composition 1 was changed to the adhesive composition shown in Table 2.
[0064] [Example 4, Comparative Example 2] Packaging Materials 4 and 6 The adhesive composition 1 was changed to the solvent-free adhesive compositions 4 and 6 shown in Table 2, and the adhesive compositions were applied at 50°C using a roll coater to form an adhesive layer without a process of volatilizing the solvent after application. The application amount of the adhesive composition was 2.0 g / m 2Packaging materials 4 and 6 were obtained in the same manner as packaging material 1, except that the aluminum-deposited polyester film was attached to the vapor-deposited surface of the polyester film.
[0065] <Manufacturing of packaging materials (three-layer structure B)> [Example 14] Packaging material 12 Using a gravure coater, the adhesive composition 1 was applied to a nylon film (ONBC, manufactured by Unitika Ltd., thickness 15 μm) at room temperature, and the solvent was evaporated to form an adhesive layer. The adhesive layer was bonded to the vapor deposition surface of an aluminum vapor-deposited polyester film (VM-PET1510, manufactured by Toray Advanced Film Co., Ltd., thickness 12 μm) to obtain an intermediate laminate. The solid content of the adhesive composition 1 was applied in an amount of 2.0 g / m 2 Next, the adhesive composition 1 was applied to the polyester surface of the intermediate laminate in the same manner as above, and after the solvent was evaporated, the applied surface was bonded to an unstretched polyethylene film (TUX-FCD, manufactured by Mitsui Chemicals Tocello, Inc., thickness 50 μm) to obtain a laminate. The obtained laminate was kept at 40° C. for 4 days to harden the adhesive layer, and a packaging material 12 having a structure of nylon film / urethane adhesive layer (containing ion scavenger) / aluminum vapor deposition layer / polyester film / urethane adhesive layer (containing ion scavenger) / unstretched polyethylene film was obtained.
[0066] [Examples 15 to 21, Comparative Example 5] Packaging materials 13 to 20 Packaging materials 13 to 20 were obtained in the same manner as packaging material 12, except that adhesive composition 1 was changed to the adhesive composition shown in Table 4.
[0067] <Evaluation of packaging materials (three-layer structure)> The following evaluations were carried out on the resulting packaging materials having the three-layer structures A and B. The results are shown in Tables 2 and 4.
[0068] (Laminate appearance) The laminate appearance of the resulting three-layer packaging material was visually observed and evaluated according to the following criteria. A: No streaks or unevenness in the adhesive layer (good) A -: No streaks or unevenness in the adhesive layer, but slight white spots (usable) B: Streaks or unevenness have occurred in the adhesive layer (unusable)
[0069] (Appearance of deposition layer) 20 g of fabric softener (Confort, manufactured by Unilever) was applied to an area of 9 cm x 13 cm on the NY film surface of the resulting three-layer packaging material and stored at 40°C for 3 days. After this, the fabric softener was wiped off and the appearance of the aluminum vapor-deposited layer was visually observed and evaluated according to the following criteria. A: No abnormalities in appearance, metallic luster is maintained (usable) A-: The aluminum vapor deposition layer is slightly corroded, but the metallic luster is maintained (usable). B: The aluminum vapor deposition layer has corroded and lost its metallic luster (unusable).
[0070] [Table 2]
[0071] From the results in Table 2, the packaging material of the present invention in which a urethane adhesive layer containing an ion trapping agent (X) is in contact with an aluminum vapor-deposited layer suppresses corrosion of the aluminum vapor-deposited layer even when a softener is attached to the outside, and the appearance of the vapor-deposited layer is excellent. In addition, whether a solvent-based or solventless adhesive composition is used, the laminate appearance is excellent. Example 1, in which the ion trapping agent is in the range of 0.2 to 10 mass% relative to the urethane adhesive layer, had a superior laminate appearance compared to Example 12, which is outside the range.
[0072] [Table 4]
[0073] From the results in Table 4, even when the amount of adhesive applied was small, the packaging material of the present invention in which a urethane adhesive layer containing an ion scavenger (X) was in contact with an aluminum vapor-deposited layer suppressed corrosion of the aluminum vapor-deposited layer and had an excellent appearance of the vapor-deposited layer. In particular, Examples 14, 19, and 21, in which the particle size of the ion scavenger was 0.1 to 1.0 μm and the content was 0.2 to 10 mass%, had excellent laminate appearance and vapor-deposited layer even when the adhesive weight after drying was small.
[0074] <Manufacturing of packaging containers> [Example 5] Packaging container 1 Using a laminator, adhesive composition 1 was applied to a stretched polypropylene film (Futamura Chemical Industry Co., Ltd. FOR, thickness 25 μm) at room temperature, and the solvent was evaporated to form an adhesive layer. The adhesive layer was attached to the vapor deposition surface of an aluminum vapor-deposited stretched polypropylene film (Toray Film Processing Co., Ltd. MS33, thickness 15 μm) to obtain a laminate. The solid content of adhesive composition 1 was applied in an amount of 3.5 g / m2. 2 The obtained laminate was kept at 40°C for 4 days to harden the adhesive layer, and a packaging material having a structure of biaxially oriented polypropylene (hereinafter, OPP) film / urethane adhesive layer (containing an ion scavenger) / aluminum vapor deposition layer / OPP film was obtained. Next, the OPP films of the obtained packaging material that were in contact with the aluminum vapor deposition layers were placed face to face and heat sealed to obtain a packaging container 1 that was a pouch of 9 cm x 13 cm.
[0075] [Examples 6, 7, and 22-26, Comparative Example 3] Packaging containers 2, 3, 5, and 7-11 Packaging containers 2, 3, 5 and 7 to 11 were obtained in the same manner as packaging container 1, except that adhesive composition 1 was changed to the adhesive composition shown in Table 3.
[0076] [Example 8, Comparative Example 4] Packaging containers 4 and 6 The adhesive composition 1 was changed to the solvent-free adhesive compositions 4 and 6 shown in Table 3, and the adhesive compositions were applied at 50°C using a roll coater to form an adhesive layer without a process of volatilizing the solvent after application. The application amount of the adhesive composition was 2.0 g / m 2Packaging containers 4 and 6 were obtained in the same manner as packaging container 1, except that the aluminum-deposited surface of the stretched polypropylene film was attached.
[0077] <Evaluation of packaging containers> The resulting packaging containers (pouches) were evaluated as follows, and the results are shown in Table 3.
[0078] (Laminate appearance) The laminate appearance of the obtained pouch was visually observed and evaluated according to the following criteria. A: No streaks or unevenness in the adhesive layer (good) A - : No streaks or unevenness in the adhesive layer, but slight white spots (usable) B: Streaks or unevenness have occurred in the adhesive layer (unusable)
[0079] (Appearance of deposition layer) The pouch was filled with 20 g of conditioner (LUX, manufactured by Unilever) and stored at 60°C for one week. The appearance of the aluminum vapor deposition layer was then visually observed from the outside of the pouch and evaluated according to the following criteria. A: No abnormalities in appearance, metallic luster is maintained (usable) A-: The aluminum vapor deposition layer is slightly corroded, but the metallic luster is maintained (usable). B: The aluminum vapor deposition layer has corroded and lost its metallic luster (unusable).
[0080] [Table 3]
[0081] From the results in Table 3, in the packaging container using the packaging material of the present invention in which the urethane adhesive layer containing the ion trapping agent (X) is in contact with the aluminum vapor deposition layer, the corrosion of the aluminum vapor deposition layer due to the contents is suppressed, and the appearance of the vapor deposition layer is excellent. In addition, whether a solvent-based or solventless adhesive composition is used, the laminate appearance is excellent. Example 5, in which the ion trapping agent is in the range of 0.2 to 10 mass% relative to the urethane adhesive layer, had a superior laminate appearance compared to Example 25, which is outside the range.
Claims
1. A packaging material having at least a configuration in which a first substrate, a urethane adhesive layer, and a second substrate are laminated in this order from the outside, At least one of the first substrate and the second substrate is a substrate having an aluminum vapor-deposited layer, The urethane adhesive layer contains an ion scavenger (X), The ion scavenger (X) is an organic compound, A packaging material comprising a urethane adhesive layer provided in contact with the aluminum vapor deposition layer.
2. 2. The packaging material according to claim 1, wherein the urethane adhesive layer is a cured product of an adhesive composition containing a polyol component (A) and a polyisocyanate component (B).
3. The packaging material according to claim 2 , wherein the polyol component (A) comprises at least one member selected from the group consisting of polyester polyols and polyether polyols.
4. The packaging material according to any one of claims 1 to 3, wherein the content of the ion scavenger (X) is 0.2 to 10 mass% based on the mass of the urethane adhesive layer.
5. The packaging material according to any one of claims 1 to 4, wherein the first substrate and the second substrate each have a polyolefin resin layer.
6. A packaging container, at least a part of which is formed from the packaging material according to any one of claims 1 to 5.
Citation Information
Patent Citations
Resin composition for moisture barrier adhesive, and adhesive
JP2013127033A
Gas barrier multilayer film having layer including aluminum vapor deposition layer or aluminum foil
JP2013147014A
Polyurethane resin composition and adhesive composition, laminate, and printed wiring board using same
WO2015046032A1
Urethane-based adhesive, polyol composition for urethane-based adhesive, polyisocyanate composition for urethane-based adhesive, hardened material of urethane-based adhesive, and lamination film
WO2017221661A1